Prediksi Jumlah Ternak Ayam Ras Petelur Berdasarkan Keuntungan Hasil Produksi Menggunakan Metode Inverse Regression Classic - Sonia Humaira; Helma Helma (Journal of Mathematics UNP, 2020)
Abstract–The business of purebreed chicken has a lot of defiance that become a disturbances of purebreed chicken bussines. The cost for production are higher than the livestock produce. This would results in tremendous loss for the farm owners. This problem can be explained by using the classic regression inverse method so that the profit of purebreed chicken can be maximized from the amount of the livestock which available. So the value of the  can be predicted from the prediction model in the  response variable. The purpose of this research is to formed two hose model prediction for the amount of the livestock of purebreed chicken based on production profits. This research uses primary data obtained from 15 purebreed chicken farms in Padang Pariaman Regency. The result of this research acquired the amount of livestock that must be provided depend on the benefits of production. Keywords– Purebreed chicken, Regression Forecasting, Inverse Regression Classic.